2017
DOI: 10.1371/journal.pone.0184382
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sterols and depressive symptom severity in a population-based cohort

Abstract: Convergent evidence strongly suggests major depressive disorder is heterogeneous in its etiology and clinical characteristics. Depression biomarkers hold potential for identifying etiological subtypes, improving diagnostic accuracy, predicting treatment response, and personalization of treatment. Human plasma contains numerous sterols that have not been systematically studied. Changes in cholesterol concentrations have been implicated in suicide and depression, suggesting plasma sterols may be depression bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, there are no commonly accepted depression biomarkers to improve diagnostic accuracy or to evaluate severity ratings [ 3 ]. Although the cellular and molecular mechanisms underlying the pathophysiology of depression are not been fully elucidated, there have been increasing interests in associations between depression and changes in various biochemical pathways, including inflammatory, neurotrophic and hypothalamic-pituitary-adrenal (HPA) axis alterations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no commonly accepted depression biomarkers to improve diagnostic accuracy or to evaluate severity ratings [ 3 ]. Although the cellular and molecular mechanisms underlying the pathophysiology of depression are not been fully elucidated, there have been increasing interests in associations between depression and changes in various biochemical pathways, including inflammatory, neurotrophic and hypothalamic-pituitary-adrenal (HPA) axis alterations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subject characteristics are summarized in Table 1 . Sample size was estimated based on the effect size we had observed in plasma samples in a previous study [ 15 ]. Collection of postmortem brains by the Dallas Brain Collection was approved by UT Southwestern Institutional Review Board.…”
Section: Materials Subjects and Methodsmentioning
confidence: 99%
“…Additionally, a putative association between low plasma cholesterol and depression or suicide has been suggested by several lines of investigation [ 9 14 ]. In light of these findings, we previously investigated associations between plasma sterols and depressive symptoms in a large, population-based cohort, as potential biomarkers [ 15 ]. We found that lower concentrations of the cholesterol precursor desmosterol and higher concentrations of another precursor, 7-dehydrocholesterol (7DHC), were predictive of moderate to severe depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…While endogenous cholesterol synthesis is essential for brain development, intact cholesterol metabolism is also critical for normal functioning of the adult brain ( 19 ). In the elderly, high brain cholesterol is associated with better memory function, while low cholesterol is associated with an increased risk for depression ( 20 , 21 ). Dysfunction of the cholesterol biosynthesis pathways and/or metabolism might contribute to a number of psychiatric and neurodegenerative disorders including major depression, bipolar disorder, schizophrenia, Huntington’s disease, and Alzheimer’s disease ( 22 25 ).…”
Section: Cholesterol and The Brainmentioning
confidence: 99%